RADSex: A computational workflow to study sex determination using restriction site‐associated DNA sequencing data. (9th March 2021) - Feron, Romain; Pan, Qiaowei; Wen, Ming; Imarazene, Boudjema; Jouanno, Elodie; Anderson, Jennifer; Herpin, Amaury; Journot, Laurent; Parrinello, Hugues; Klopp, Christophe; Kottler, Verena A.; Roco, Alvaro S.; et al.
Abstract: The study of sex determination and sex chromosome organization in nonmodel species has long been technically challenging, but new sequencing methodologies now enable precise and high‐throughput identification of sex‐specific genomic sequences. In particular, restriction site‐associated DNA sequencing (RAD‐Seq) is being extensively applied to explore sex determination systems in many plant and animal species. However, software specifically designed to search for and visualize sex‐biased markers using RAD‐Seq data is lacking. Here, we present RADSex, a computational analysis workflow designed to study the genetic basis of sex determination using RAD‐Seq data. RADSex is simple to use, requires few computational resources, makes no prior assumptions about the type of sex‐determination system or structure of the sex locus, and offers convenient visualization through a dedicated R package. To demonstrate the functionality of RADSex, we re‐analysed a published data set of Japanese medaka, Oryzias latipes, where we uncovered a previously unknown Y chromosome polymorphism. We then used RADSex to analyse new RAD‐Seq data sets from 15 fish species spanning multiple taxonomic orders. We identified the sex determination system and sex‐specific markers in six of these species, five of which had no known sex‐markers prior to this study. We show that RADSex greatly facilitates the study of sex determination systems in nonmodel species thanks to its speed of analyses, low resource usage, ease of application and visualization options. Furthermore, our analysis of new data sets from 15 species provides new insights on sex determination in fish.